Innovations in Peace and Education Praxis Transdisciplinary Reflections and Insights - Archer, David Tim; Hajir, Basma; McInerney, William W. (Routledge Research in International and Comparative Education, 2023)
Affect; critical pedagogy; education research; epistemology; peace education; peacebuilding education; philosophy of education